Reliable Measurement of Perovskite Solar Cells. Issue 47 (21st January 2019) - Wang, Yanbo; Liu, Xiao; Zhou, Zhongmin; Ru, Pengbin; Chen, Han; Yang, Xudong; Han, Liyuan
Abstract: Perovskite solar cells (PSCs) have undergone an incredibly fast development and attracted intense attention worldwide owing to their high efficiency and low‐cost fabrication. However, it is challenging to make a reliable measurement of PSCs, which creates great difficulty for researchers to compare and reproduce published results. Herein, the major measurement methods and key factors affecting evaluation of PSCs are summarized, such as hysteresis in current–voltage measurement, calibration of solar simulators for less mismatch in spectra and light intensity, and the area for the calculation of current density and power conversion efficiency. PSCs are also compared with n–i–p or p–i–n structures that exhibit different feedback under the same measurement methods. Finally, a measurement proposal is provided to help researchers obtain reliable measurement results close to those certified by public test centers. Abstract : Rapid advancement of perovskite solar cells confronts the challenges of reliable measurement, which is important for data analysis and results reproduction. Major measurement methods and the key factors affecting evaluation are summarized. A measurement proposal is provided to help researchers obtain reliable measurement results close to those certified by public test centers.